Housing price prediction using neural network - Sng, Pei Wen (2018)
This research applies the artificial neural network (ANN) models to predict the resale flat prices in Singapore. The study consists of three major sections. In Section 1, factors affecting resale flat prices and data collection process is shown; in Section 2, ANN with LM algorithm is used to predict the resale price based on the housing characteristics; in Section 3, ANN with RVFL is used to predict the resale price based on the housing characteristics. Data from 2016 onwards are used for training, testing and validation. The results show that the ANN with LM algorithm can produce a good prediction, with regression values higher than 0.9 in all the cases tested for this research.